Under-expression of VHL and over-expression of HDAC-1, HIF-1α, LL-37, and IAP-2 in affected skin biopsies of patients with psoriasis - Tovar-Castillo, Laura E.; Cancino-Díaz, Juan C.; García-Vázquez, Francisco; Cancino-Gómez, Francisco G.; León-Dorantes, Gladys; Blancas-González, Fernando; Jiménez-Zamudio, Luis; García-Latorre, Ethel; Cancino-Díaz, Mario E. (International journal of dermatology, 2007)
Background  A feature of psoriasis is the rapid proliferation of keratinocytes, during which apoptosis is blocked and angiogenesis starts. It is known that tumor hypoxic cells produce histone deacetylase‐1 (HDAC‐1), which up‐regulates hypoxia‐inducible factor‐1α (HIF‐1α) and down‐regulates von Hippel–Lindau (VHL) protein by up‐regulating vascular endothelial growth factor (VEGF) expression. It has been reported recently that the porcine peptide PR39 (homologous to human LL‐37) has angiogenic and antiapoptotic activity. Thus, LL‐37, induced by insulin‐like growth factor‐1 (IGF‐1), could help in the production of VEGF. PR39 also induces the expression of inhibitor of apoptosis protein‐2 (IAP‐2), which blocks apoptosis. The purpose of this work was to analyze whether these genes and their proteins are expressed in psoriatic biopsies. Methods  Using semiquantitative reverse transcriptase‐polymerase chain reaction (RT‐PCR) messenger RNA (mRNA) expression and immunohistochemical staining, we studied VHL, IAP‐2, and related genes in skin biopsies from psoriatic patients and healthy subjects. Results  An over‐expression of the mRNA for HDAC‐1, HIF‐1α, LL‐37, and IGF‐1 in psoriatic skin, in comparison with skin from healthy subjects, was found. The antiangiogenic VHL mRNA and protein were under‐expressed in psoriatic skin and highly expressed in healthy skin. The antiapoptotic IAP‐2 was over‐expressed in dermal endothelial cells from psoriatic skin. The pro‐apoptotic Bax, Fas, and FasL mRNAs were expressed. Conclusions  These findings suggest that there could be an association of HDAC‐1, HIF‐1α, LL‐37, VHL, and IAP‐2 with angiogenic and apoptotic mechanisms in psoriasis.